Subclinical Bacteriuria in Older Cats and its Association with Survival - White, J.D. (J Vet Intern Med, 2016)
BACKGROUND: Bacterial urinary tract infections are uncommon in cats in general but the prevalence increases to 29% in older cats with comorbidities (Veterinary Clinical Pathology 2008, 37, 317; Journal of Feline Medicine & Surgery 2007, 9, 124; Veterinary Microbiology 2009, 136, 130). Frequently, the infections are subclinical. The clinical relevance of subclinical bacteriuria (SB) is uncertain, and the optimal treatment requires clarification. OBJECTIVE: Prospective, observational study to: (i) identify the prevalence and incidence count of SB in older (≥7 years), nonazotemic cats, (ii) evaluate specific risk factors for SB, and (iii) investigate the potential relationship between untreated SB and survival. ANIMALS: Sixty‐seven, nonazotemic cats were tested on 5 occasions over 3 years. METHODS: Urine samples were obtained by cystocentesis for quantitative urine culture and blood samples for measurement of serum creatinine concentration. Episodes of SB were not treated. Serum creatinine concentration, body weight, urine specific gravity, sex, and age were evaluated as potential risk factors for a positive urine culture. The association between urine culture results and survival was evaluated with Cox's proportional hazard model. RESULTS: A total of 256 urine samples was obtained. The prevalence of SB varied between 10 and 13%, and incident infections were uncommon. Female cats were 21 times more likely to have a positive urine culture than were male cats (odds ratio [OR], 21.2; confidence interval [CI], 4.1–110; P = .00028). Subclinical bacteriuria was not significantly associated with survival. CONCLUSION AND CLINICAL IMPORTANCE: Subclinical bacteriuria is common in nonazotemic, older cats. Although antimicrobial treatment was withheld, the presence of SB was not adversely associated with survival.